Mapait Ang Ugat Ng Asukal - Nicor, Rocky O. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
“Mapait ang Ugat ng Asukal” is a theatrical experiment in the style of a documentary that explores the complex historical and social aspects of Negros Occidental. The drama, which is set against the backdrop of Spanish colonization, examines how a brave resistance to the Spaniards that led to liberation also unintentionally strengthened institutional tyranny in the area through the hacienderos. The play intends to shed light on the complexity of freedom and its aftermath, particularly in the context of power dynamics and land ownership, using a combination of theatrical elements and documentary-style narration.